Testing the stakeholders approach for historical cases of private patrimonies. The Osuna Ducal Estate (1590-1633) - López Manjón, Jesús D. (De Computis, Revista Española de Historia de la Contabilidad., 2012)
The main aim of this paper is to test the validity of the stakeholder approach in a historical context different to the one in which it was originally developed. Specifically the late 16th and early 17th centuries. Furthermore, the paper applies this framework to the management of a private wealth, the Osuna ducal Estate, which is also a singularity with regards to previous works that have used this approach. For this purpose, we focus on the identification and salience of stakeholders. From 1590 onwards, the ducal Estate wealth was seized by the Government due to its high level of indebtedness. Since the changes in the ducal Estate management and accounting were promoted by creditors and the Crown, it seems that the stakeholder approach could be useful to analyse the case.